Aryl–aryl coupling in a polycyclic aromatic hydrocarbon with embedded tetracoordinate boron centre. Issue 20 (8th May 2019) - Kirschner, Sven; Bao, Song-Song; Fengel, Melina K.; Bolte, Michael; Lerner, Hans-Wolfram; Wagner, Matthias
Abstract : An oxaboraphenanthrene is generated from a 9, 10-dihydro-9, 10-diboraanthracene through boron extrusion/C–C coupling upon addition of mesityl lithium and chromatographic workup. Abstract : The addition of 2 eq. of MesLi to the biphenylene-containing 9, 10-dihydro-9, 10-diboraanthracene (DBA)2 results in the formation of the corresponding oxaboraphenanthrene3 after column chromatography under ambient conditions. In the initial step, the anionic B–Mes monoadduct of2 is generated, which eliminates a formal [Mes2 B:] − ion with concomitant C–C-bond formation (room temperature, 18 h). The resulting biphenylene-containing borafluorene4 is still sufficiently Lewis acidic to add the second equivalent of MesLi ([4 Mes] − ). Using pristine 9-mesityl-9-borafluorene as a model system, we confirmed that both4 and [4 Mes] − should be capable of inserting an oxygen atom to furnish the observed oxaboraphenanthrene scaffold. The biphenylene-containing oxaboraphenanthrene3 is a yellow compound with an absorption maximum at λ max = 450 nm. Similar to its DBA analogue2, 3 shows no photoluminescence.